The early wear susceptibility of cementum, enamel and dentine in vitro. (December 2022) - Al Shammari, M.; Helmi, A.; Jadeja, S.; Bartlett, D.; O'Toole, S.
Highlights: Contrary to current theory, cementum may be the least susceptible surface to erosive tooth wear. Dentine does not wear at a faster rate than enamel under erosion dominant conditions. Abstract: Objectives: To assess the differential early wear susceptibility of cementum, enamel and dentine at a micron level. Methods: Whole human molar buccal surfaces incorporating natural enamel and cementum (n = 20) confirmed by imaging (digital microscopy: Keyence, VHX-7000 Milton Keynes, UK), were mounted, scanned (profilometry: XYRIS 4000, Taicaan, Southampton, UK), and allocated to receive erosion (citric acid, pH 2.7, 30 min (n = 10)) or erosion/abrasion challenges (3 cycles of (citric acid, pH 2.7, 10 min, 60 300 g linear abrasion strokes), n=10). Samples were polished and the experiment repeated on polished enamel, and polished coronal and radicular dentine within the same tooth. Profilometric wear data were obtained using superimposition: GeoMagic (3Dsystems, Darmstadt, Germany) and subtraction: MountainsMap (DigitalSurf, Besancon, France). Data were normal. A general linear model was used to assess differences between groups and substrates. Results: The mean step height (SD) for natural enamel was 8.82 μm (2.53) for erosion and 11.48 μm (2.95) for erosion/abrasion. For natural cementum, the mean step height was 6.00 μm (2.29) for erosion and 4.67 μm (1.58) for erosion/abrasion. Dentine step heights ranged from 7.20 μm (1.53) for erosion and 9.79 μm (1.01) for erosion/abrasion with no statistical differences in dentine wear. Natural cementum surfaces had the lowest wear (p<0.001). Dentine had significantly less wear than natural enamel (p<0.02). Conclusions: Cementum surfaces demonstrated the most wear resistance, followed by dentine under erosion dominant conditions in this in vitro study. Further in-vivo investigations are needed to confirm the intraoral stability of cementum. Clinical Significance: Cementum may be the least susceptible of dental substrates to wear and dentine does not wear at a faster rate than enamel under erosive conditions. This adds to our knowledge on the development of non-carious cervical lesions and questions whether wear rates will accelerate once dentine is exposed.